The Role of the Two-Component QseBC Signaling System in Biofilm Formation and Virulence of Hypervirulent Klebsiella pneumoniae ATCC43816 - Lv, Jingnan; Zhu, Jie; Wang, Ting; Xie, Xiaofang; Wang, Tao; Zhu, Zhichen; Chen, Liang; Zhong, Fengyun; Du, Hong (Frontiers in Microbiology, 2022)
Hypervirulent Klebsiella pneumoniae (hvKP) is an evolving infectious pathogen associated with high mortality. The convergence of hypervirulence and multidrug resistance further challenges the clinical treatment options for K. pneumoniae infections. The QseBC two component system (TCS) is a component of quorum-sensing regulatory cascade and functions as a global regulator of biofilm growth, bacterial motility and virulence in Escherichia coli. However, the functional mechanisms of QseBC in hvKP have not been reported, and we aim to examine the role of QseBC in regulating virulence in hvKP strain ATCC43816. The CRISPR-Cas9 system was used to construct qseB, qseC and qseBC knockout in ATCC43816. No significant alterations in the growth and antibiotic susceptibility were detected between wild-type and mutants. The deletion of qseC led to an increase of biofilm formation， resistance to serum killing and high mortality in G. mellonella model. RNAseq differential gene expression analysis exhibited that genes associated biofilm formation (glgC, glgP, glgA, gcvA, bcsA, ydaM, paaF, ptsG), bacterial type Ⅵ secretion system (virB4, virB6, virB10, vgrG, hcp), biosynthesis of siderophore (entC, entD, entE) were significantly up-regulated in comparison with the wild-type control. In addition, qseB, ygiW (encode OB-family protein) and AraC family transcriptional regulator IT767_23090 genes showed highest expressions in the absence of QseC, which might be related to the increased virulence. The study provided new insights into the functional importance of QseBC in regulating virulence of hvKP.